Via avis the Candaba adaptive Wetland Conservation and Recreation Complex - Lopez, Jharren O.; Chua, Johannes V.F. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
The increasing threat on our environment has now reached its alarming state. Various species of flora and fauna are now in danger of being extinct because of the massive destructions on their habitats caused by human actions. One of the most diverse ecosystems in the world, the wetlands, is currently facing the same fate. Existing laws and legal provisions which are meant to safeguard these wildlife and their habitats often lacks the teeth to administer the policies. The need for collective action to reinforce these policies for the further protection of wetlands is seen to be the best solution to better the current situation of the said ecosystem. It has been realized that government policies alone isn't sufficient to protect these ecosystems, it needs to be tied up in a program wherein it shall capture the attention of the general public and various sectors to collectively exert the necessary effort to salvage the remaining wetlands and the wildlife that benefits from it. Hence, the role of tourism to promote awareness and education and active conservation in the area would be the main key towards this solution. This design thesis, in collaboration with a B Landscape Architecture student Mr. Mackie Bretana with his undergraduate thesis entitled as Into the Hinterlands : Utilizing Candaba Swamp Through Seasonal Recreation Programming and Sustainable Toursim, shall highlight the importance of a well planned development which is anchored on a comprehensive research methodology to make sure that its feasibility and practicability would be adequate for the sensitive ecosystem. Furthermore, this thesis shall provide a design for an adaptive type of architecture that would be not only provide a good venue for ecotourism but would also correspond contextually to the requirement needed in this kind of site. Generally, this thesis hopes to serve as a design guide for construction and development on wetland ecosystems.
Includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Wetland conservation; Wetland ecology